A Study on Missing Data Management - Mitra, Malay; Samanta, RK (International Journal of Computer Sciences and Engineering, 2025)
Missing data, a persistent problem in most scientific research, should be handled very carefully, as role of data are vital in every analysis. Mishandling missing values may cause distorted analysis or may generate biased results. Valid and reliable models require good data preparation. Dozens of techniques have been proposed by methodologists to address the problem. Appropriate method should be taken into consideration for a particular study in order to achieve efficient and valid analysis. In this study we discuss different methods to handle missing data and compare three imputation methods: Arithmetic Mean Imputation, Regression Imputation and Multiple Imputation using EMB algorithm, performed on three data sets from UCI repository under the assumption of MAR based on Root Mean Square Error (RMSE) as an evaluation criteria.